2011
DOI: 10.1186/1742-2094-8-43
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high dose interferon-β1a on plasma microparticles: Correlation with MRI parameters

Abstract: ObjectivesWe previously reported a correlation between levels of microparticles carrying CD31 (PMP CD31+) and disease activity in MS. However, the effects of long term (12 month) treatment with high dose, high frequency interferon-β1a (Rebif™) on plasma levels of PMPCD31+, PMPCD146+, and PMPCD54+ and MRI measures of disease activity have not yet been assessed.MethodsDuring this prospective 1-year study, we used flow cytometry to measure changes in plasma microparticles (PMP) bearing CD31 (PMPCD31+), CD146 (PMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
0
23
2
1
Order By: Relevance
“…Similarly, other groups have reported that MCAM EMPs do not reflect endothelial damage induced by INFß-1, although PECAM EMPs do 35. MCAM is also expressed on a subset of T- and B-lymphocytes, NK cells36 and pericytes 37.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, other groups have reported that MCAM EMPs do not reflect endothelial damage induced by INFß-1, although PECAM EMPs do 35. MCAM is also expressed on a subset of T- and B-lymphocytes, NK cells36 and pericytes 37.…”
Section: Discussionmentioning
confidence: 74%
“…Several endothelial and platelet ECAMs have now been described as MP markers in MS including CD51/CD61 (αV/β3-integrin), CD31 (platelet endothelial cell adhesion molecule-1) [7] and CD54 (intercellular adhesion molecule-1/ICAM-1) [7]. CD31 is an immunoglobulin-superfamily ECAM constitutively expressed on apical and junctional endothelial surfaces, and on platelets, myeloid cells and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…CD31 is an immunoglobulin-superfamily ECAM constitutively expressed on apical and junctional endothelial surfaces, and on platelets, myeloid cells and lymphocytes. CD31 + MPs are released during MS exacerbations [4]; and appear to correlate with early changes in BBB disruption and axonal injury, often abating during remission and therapy [7]. Another MP marker, CD51 (integrin αV) forms several complexes which bind fibronectin and vitronectin and regulates vascular structure and stability [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One step in the right direction would be, that more researchers would appreciate the possibility to upload their -even though small-data sets with expression data and clinical data. This would enable researchers to utilize these data for [37] pNF-H (+) Cellular [93,94] plasma endothelial microparticles (+) miRNA [90] hsa-miR-1826 (+) hsa-miR-572 (+) hsa-miR-1979 (-) hsa-miR-614 (+) hsa-miR-22 (+) hsa-miR-648 (+) Serum and PBMC miRNA [25,90] hsa-miR-422a (+) PBMC miRNA [25][26][27]71,72,89] hsa-miR-19b (CD4+CD25+ cells) (+) hsa-miR-17-5p (+) hsa-miR-25 (CD4+CD25+ cells) (+) hsa-miR-18-5p (+) hsa-miR-1275 (+) hsa-miR-186-5p (-) hsa-miR-145-5p (+) hsa-miR-20a-5p (+) hsa-miR-491-5p (+) hsa-miR-20b-5p (+) hsa-miR-584-5p (+) hsa-miR-223-3p (+) hsa-miR-664-3p (+) hsa-miR-142-3p (+) mRNA [1] ATP7A ( Fas/FasL mRNA [5] ILT3 (-; mono.) miRNA [25,71,72] hsa-miR-18b (+) hsa-miR-599 (+) hsa-miR-96-5p (+; remission) Disease activity and treatment response…”
Section: Discussionmentioning
confidence: 99%